2011
DOI: 10.1063/1.3658046
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of atactic polystyrene adsorbed onto solid surfaces

Abstract: In the present work, we are studying the local conformation of chains in a thin film of polystyrene adsorbed on a solid substrate by using atomistically detailed simulations. The simulations are carried out by using the readily available and massively parallel molecular dynamics code known as LAMMPS. In particular, a special emphasis is given to the density and orientation of side chains (which consist of phenyl groups and methylene units) at solid/polymer and polymer/vacuum interfaces. Three types of substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 35 publications
6
34
2
Order By: Relevance
“…On the other hand, a shoulder peak of N 1s at 397.8 eV is more dominant in P2VP­(spin) TA , as indicated with the green arrow in the first and second rows of Figure c, respectively. There are various possibilities for the origin of this peak, and the most probable case is that a hydroxyl group of the native oxide layer interacts with the π bond in the aromatic pyridine ring, thus forming a well-known hydrogen bonding of π···H–O. It should be noted that the origins of the H-bonding for adsorbed layers can be different depending on how the adsorbed layers are formed: whether they are transferred from the air/water interface or obtained from a spin-coated film. A thorough and complete XPS analysis is provided in the Supporting Information (see the Discussions section; Figures S6–S8, and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a shoulder peak of N 1s at 397.8 eV is more dominant in P2VP­(spin) TA , as indicated with the green arrow in the first and second rows of Figure c, respectively. There are various possibilities for the origin of this peak, and the most probable case is that a hydroxyl group of the native oxide layer interacts with the π bond in the aromatic pyridine ring, thus forming a well-known hydrogen bonding of π···H–O. It should be noted that the origins of the H-bonding for adsorbed layers can be different depending on how the adsorbed layers are formed: whether they are transferred from the air/water interface or obtained from a spin-coated film. A thorough and complete XPS analysis is provided in the Supporting Information (see the Discussions section; Figures S6–S8, and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason in the last few years several simulation works concerning the properties of various polymer-graphene (or polymer-graphite) nanostructured systems have appeared in the literature. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The study of the dynamics of polymer chains close to graphene layers is of special importance, since friction at the interface determines the dynamical, the rheological as well as the mechanical properties of the hybrid system.…”
Section: Introductionmentioning
confidence: 99%
“…For a series of different polymers authors found that both CNTs and GNSs induce crystallization of alkane molecules in the range of temperatures [400-500]K, while CNT's presented a stronger effect on crystallization. The structure of atactic polystyrene (PS) on three different substrates, a-quartz, amorphous silica and graphite has been also studied through detailed atomistic simulations by Tatek et al (Tatek et al 2011). In this work the effect of the type of the different surfaces on the density, the structure and the conformational properties of PS has been discussed.…”
Section: Introductionmentioning
confidence: 99%